2013
DOI: 10.1037/a0031794
|View full text |Cite
|
Sign up to set email alerts
|

Social networking ethics: Developing best practices for the new small world.

Abstract: Emerging trends online, and especially in social network sites, may be creating an environment for psychologists where transparency is increasingly unavoidable. Thus, most psychological practitioners may now have to engage in small world ethics-ethical acuity that requires an application of ethical principles to the increasingly interconnected and transparent world that is burgeoning from online culture. Fortunately, rural psychology has already provided a helpful roadmap for how to demonstrate flexibility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…These are no longer particularly novel concepts, as this literature has developed over the past decade and states are increasingly introducing legislation to facilitate the provision of telehealth services (see, e.g., New Jersey's Bill S291/652/1954, which was recently signed into law by Governor Christie). A more contemporary issue, however, is mental health professionals' use of the Internet to gather information about their clients (see, e.g., Asay & Lal, 2014;Clinton, Silverman, & Brendel, 2010;DiLillo & Gale, 2011;Harris & Robinson Kurpius, 2014;Kaslow, Patterson, & Gottlieb, 2011;Kolmes & Taube, 2014;Lannin & Scott, 2013;Pham, 2014;Powell & Clarke, 2006).…”
Section: Mental Health Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…These are no longer particularly novel concepts, as this literature has developed over the past decade and states are increasingly introducing legislation to facilitate the provision of telehealth services (see, e.g., New Jersey's Bill S291/652/1954, which was recently signed into law by Governor Christie). A more contemporary issue, however, is mental health professionals' use of the Internet to gather information about their clients (see, e.g., Asay & Lal, 2014;Clinton, Silverman, & Brendel, 2010;DiLillo & Gale, 2011;Harris & Robinson Kurpius, 2014;Kaslow, Patterson, & Gottlieb, 2011;Kolmes & Taube, 2014;Lannin & Scott, 2013;Pham, 2014;Powell & Clarke, 2006).…”
Section: Mental Health Servicesmentioning
confidence: 99%
“…For example, Clinton et al (2010) provided six questions for healthcare professionals to ask themselves before searching the Internet for information about their clients and suggested that, when contemplating searching for client information, professionals consider their motivations, along with the associated risks and benefits. Lannin and Scott (2013) identified similarities between ethical challenges faced by practitioners in the online world and those who practice in rural and other "small world" settings, and suggested that this framework could inform practitioners in online contexts. Pirelli (2017) recently addressed the need for professional accountability in online contexts by embracing transparency in distinguishing between professional and personal communications.…”
Section: Mental Health Servicesmentioning
confidence: 99%
“…Although school psychologists are afforded autonomy regarding their online behavior, they need to be cautious with regard to how their private behavior may intersect with their professional work (Lannin & Scott, ). Both the APA and NASP codes of ethics are written to protect children and families, consumers of school psychological services, and the public's trust in the school psychology profession.…”
Section: Private Conduct and Behaviormentioning
confidence: 99%
“…However, most respondents also thought it was acceptable to search for clients out of simple curiousity and report that they and their colleagues engage in these types of searches. This may suggest that workers do not see social media searches as a factor that may impact goals of engagement, as suggested by Lannin and Scott (2013), or do not see a client privacy concern related to this behavior.…”
Section: What Beliefs About Social Media Inform Child Welfare Workersmentioning
confidence: 99%
“…If a client finds out about a social media search it may be seen as a boundary violation (Lannin & Scott, 2013) and disrupt goals related to family engagement. This lens suggests that child welfare workers might avoid social media searches in cases where social media does not have a clear role in child safety.…”
Section: Tensions Of Social Media Use In Child Welfare: Safety Versusmentioning
confidence: 99%